Sorption Studies of Chromium(VI) and Mercury(II) by High Temperature Activated Carbon from Syzygium Jambolanum Nut - S. Sophie Beulah; K. Muthukumaran (E-Journal of Chemistry)
High temperature activated Syzygium Jambolanum nut carbon (HSJC) has been effectively used for the removal of Cr(VI) and Hg(II) from aqueous solution by batch experiments. Effect of pH, carbon dose and equilibration time were determined. Adsorption followed Freundlich and Langmuir isotherms. Kinetic studies indicated that the removal process followed reversible first order equation. Desorption of Cr(VI) was done with 1 M NaOH and 10% H2O2 mixture and Hg(II) with 2% Na2S in 1% NaOH. The performance of HSJC was compared with a commercial activated carbon (CAC).